2012
DOI: 10.1126/scitranslmed.3003841
|View full text |Cite
|
Sign up to set email alerts
|

Instructive Nanofiber Scaffolds with VEGF Create a Microenvironment for Arteriogenesis and Cardiac Repair

Abstract: An intramyocardial microenvironment was created using nanofibers and VEGF for endogenous cardiac repair after infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 57 publications
2
100
1
Order By: Relevance
“…Moreover, while liposomes have been shown to accumulate experimentally in areas of MI [30,35,36], their clinical application has been hindered because they are unstable and readily interact with high-density lipoproteins in blood. Also, self-assembling nanofiber scaffolds coated with VEGF were recently shown to improve cardiac function in rat and pig models of MI by inducing arteriogenesis and recruitment of endogenous myofibroblasts and cardiomyocyte-like cells [37]. In contrast to some of these systems, PLGA MPs are advantageous because they allow local drug delivery over an extended period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while liposomes have been shown to accumulate experimentally in areas of MI [30,35,36], their clinical application has been hindered because they are unstable and readily interact with high-density lipoproteins in blood. Also, self-assembling nanofiber scaffolds coated with VEGF were recently shown to improve cardiac function in rat and pig models of MI by inducing arteriogenesis and recruitment of endogenous myofibroblasts and cardiomyocyte-like cells [37]. In contrast to some of these systems, PLGA MPs are advantageous because they allow local drug delivery over an extended period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid regeneration of new coronary blood vessels is essential for prolonging survival of the injured myocardium (2). Unraveling new sources of vascular endothelial cells in the heart provides important insights into therapeutic deployment for cardiac regeneration (3).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study by Lin et al concluded that in a porcine model the peptide nanofiber scaffold was not only a passive delivery vehicle but also improved diastolic function post-MI through reduction of fibrosis, neo-capillary formation and reduced ventricular remodeling (Lin et al, 2010). Similar studies in small animal models showed positive, yet non-significant, effects of nanofibers alone; however, combined with the incorporation of GFs or endogenous stem cell recruitment factors significantly improved cardiac function was achieved (Davis et al, 2006;Lin et al, 2012). Peptide nanofiber-based scaffolds represent a bottom-up approach to fiber formation where small, chemically synthesized oligopeptides are the building blocks.…”
Section: Nanofibrous Materials For Cardiac Tissue Repairingmentioning
confidence: 89%